Temporal Evolution of Corrosion Film Nano-Porosity and Magnesium Alloy Hydrogen Penetration in NaCl Solution. Issue 13 (14th October 2020) - Brady, Michael P.; Rother, Gernot; Frith, Matthew G.; Ievlev, Anton E.; Leonard, Donovan N.; Littrell, Kenneth C.; Cakmak, Ercan; Meyer, Harry M.; Anovitz, Lawrence M.; Davis, Bruce
Abstract : Exposures of 0.5, 1, 4, 8, and 24 h were conducted for Mg-3Al-1Zn (AZ31B) and Mg-1.5Zn-0.3Zr-<0.5Nd (ZE10A, ZEK100 type) alloys in D2 O with 5 weight% (wt%) NaCl. Multiple techniques including small angle neutron scattering (SANS) and scanning transmission electron microscopy (STEM) were used to follow the growth of nano-porous oxide-hydroxide corrosion films. On the same samples, time of flight mass spectrometry (ToF SIMS) was used to study the penetration of deuterium into the alloys in advance of the films. The SANS scattering invariants, which are proportional to the number of nanoscale features, increased approximately linearly with time for both alloys. Analysis with the polydisperse hard sphere model for fractal systems suggests that the nano-porous structures grew at all length scales assessed, but that the size distribution did not change significantly with reaction time, i.e., the film thickness increased while the nano-porosity structures remained essentially constant. Extensive penetration of deuterium into the underlying alloy was observed by ToF-SIMS for ZE10A, but not AZ31B despite similar corrosion film growth behavior. The depth profiles suggest an alloy diffusion-controlled deuterium penetration over time, which is of similar extent to that previously observed in water without NaCl. Implications for the corrosion mechanism(s) are discussed.